التوظيف الدلالي للعادات والتقاليد الجزائرية في سينما المهجر دراسة في سيميولوجيا العادات والتقاليد وعلاقتها بالسينما - بن زطة سليم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
إن كل الأنساق التواصلية تتضمن دلالات ومعاني مضمرة تقتضي التنقيب عنها ومساءلتها سيميائيا، و الفيلم السينمائي ليس بمعزل عن هذه المقاربة، خاصة إذا تحدثنا عن سينما المهجر، هذا النوع السينمائي الذي يحمل في طياته الكثير من التجاذبات بين وطن الأصل ووطن المهجر في امتداد للهوية من جهة و تناقضها من جهة أخرى، إن موضوع العادات والتقاليد في سينما المهجر، ومدى صحة تصويرها بما يتلاءم مع الأصل أو ما يجاري إنتاج المهجر. all communicative systems comprise connotations and latent meanings which call for semantic mining and accountability, where cinematic film cannot stand away from this approach, especially if we tackle the cinema of the diaspora, such type of cinema carries within a lot of contestations between the country of origin and the country of diaspora, as an extension of identity on one hand and its opposite on the other, which brought us to study the topic of customs and traditions as a conspicuous form of identity and the way they are displayed in the diaspora’s cinema , and to which extent they are portrayed conformingly to the origin or in conjunction with the production of the diaspora.